The effectiveness of acceptance and commitment-based therapy on sleep and problem solving in 14-16 year old girls - Rezaei. Rozbahani, Zahra; Chehri, Azita; Mahmoodi, Gelavij (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to evaluate the effectiveness of acceptance and commitment therapy on sleep problems and problem solving. Methods: This quasi-experimental study was a pre-test-post-test design with a control and follow-up group for 3 months. The statistical population of this study included all 14 to 16 year old female students studying in high school in Kermanshah in 1399-1400. By available sampling method, 60 female students were selected and randomly assigned to two equal groups of 20 people. Data were collected using a problem-solving questionnaire (Hepner and Patterson, 1988) and a sleep assessment questionnaire (Boyce et al., 1989). For data analysis, SPSS software version 25 was used with descriptive statistics, statistical assumptions and analysis of variance with repeated measures and Bonferroni test. Results: The results showed that acceptance and commitment treatment was significantly effective in improving problem solving skills and its dimensions in the experimental group. Also, the results showed that acceptance and commitment therapy had a positive effect on problem solving skills of the experimental group. Conclusion: Based on the findings of the present study, it can be concluded that acceptance and commitment therapy using techniques such as mental techniques. Self-observation as a context, cognitive fault techniques, values, and committed action can be used as an effective treatment to reduce sleep problems and improve problem-solving techniques in adolescent girls.